2007
DOI: 10.1002/ppap.200732302
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Double Probe Study of the Temporal Evolution of the Charge Carrier Density in a Pulsed Magnetron

Abstract: An asymmetric‐bipolar pulsed magnetron discharge was spatially studied in two dimensions with a time‐resolved Langmuir double probe. The cylindrical magnetron was equipped with an Mg target. The development of the charge carrier density during one pulse reveals the same characteristic as the two‐peak structure at the beginning of the ‘on’ phase which we have observed earlier. This temporal peak structure changes with position within the volume of the discharge between target and substrate. While the first maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The frequency ω of the fast changes in the potential is about 50 MHz. Then a response time in front of the target in the 7 magnetic trap of ∼10 ns (taking n = 5 × 10 11 cm −3 [27], T e = 5 eV) and in front of the substrate of ∼ 500 ns (taking n = 5 × 10 9 cm −3 [28], T e = 2 eV) is obtained, which is of the order of magnitude that we observed (cf figure 3). Importantly, it should be noted that the estimation shows that the response time is strongly dependent on the charge carrier density n of the local plasma.…”
Section: Methodssupporting
confidence: 56%
“…The frequency ω of the fast changes in the potential is about 50 MHz. Then a response time in front of the target in the 7 magnetic trap of ∼10 ns (taking n = 5 × 10 11 cm −3 [27], T e = 5 eV) and in front of the substrate of ∼ 500 ns (taking n = 5 × 10 9 cm −3 [28], T e = 2 eV) is obtained, which is of the order of magnitude that we observed (cf figure 3). Importantly, it should be noted that the estimation shows that the response time is strongly dependent on the charge carrier density n of the local plasma.…”
Section: Methodssupporting
confidence: 56%
“…Optical emission spectroscopy substantiated the existence of temporal density increases or high energetic electrons at these times [21,22,27]; the latter, however, could not be detected with the double probe. A spatial survey of the two maxima revealed that they were differently pronounced throughout the discharge volume [28]. The first was most intense in the bulk plasma above the magnetic null of the magnetron where most of the residual electrons which are considered uniformly distributed were accelerated.…”
Section: Energetic Spikes In T Ementioning
confidence: 99%